Du projet stratégique sino-soviétique au projet stratégique sino-américain : la Nouvelle Chine en quête d’une stratégie d’accès à l’influence planétaire - Cadart, Claude (Études internationales)

(untitled) (Institut québécois des hautes études internationales, 1979)
« From the Sino-Soviet strategic project to the Sino-American strategic project » is a purposely schematic interpretative essay on the evolution of Chinese foreign policy from 1949 to 1979 with emphasis on, the latter phase of that evolution, that of the 1969—1979 period, and more particularly on the last year of that decade, 1979.The project, both defensive and offensive, of American and Chinese co-leadership of the planet that Mao had undertaken to carry out in 1971-1972 with the encouragement of Nixon had to be more or less put aside from 1973 to 1978 because of the seriousness of the domestic crises that were successively shaking both China and the United States during those years. In 1978—79, it was able to be reactivated by Deng Xiaoping who sought, with the benediction of the White House, to add an economic and a cultural dimension to Us diplomatic and strategic dimension.It is unlikely however in the near future that the United States will consider China as other than an auxiliary aspect of the fundamental game of their relations with the most powerful of their adversary-partners, the U.S.S.R. As in the case of the Sino-Soviet strategic project that China promoted from 1949 to 1959, the Sino-American strategic project that China has sought to « sell » the United States since 1969 has not, therefore, much chance of success.